A comprehensive analysis on source-distribution-bioaccumulation-exposure risk of metal(loid)s in various vegetables in peri-urban areas of Shenzhen, China. (15th January 2022) - Wang, Beibei; Gao, Fei; Qin, Ning; Duan, Xiaoli; Li, Yujie; Cao, Suzhen
Abstract: The health risk induced by metal(loid)s in crops are becoming increasingly serious. In this study, eight major vegetables and rhizosphere soils were collected in a peri-urban area with intense electronic information manufacturing activities. The source, distribution and bioaccumulation of six typical metal(loid)s in different vegetable species were analyzed, and exposure risk through vegetable ingestion was estimated. Results showed that vegetables and agricultural soils in the study area suffered from serious metal(loid)s pollution, especially for Cd and Pb. The bioaccumulation capacity differed greatly among individual metal(loid)s and vegetable categories. In general, the highest transfer factors (TF) for Cd, Pb, and As were found in leafy vegetables, while leguminous vegetables had the highest TF of Cu and Zn and root vegetables had the highest TF for Cr. Significant correlations were found between concentrations in vegetables and rhizosphere soils for most metal(loid)s, the exceptions being Pb and Zn. The enrichment of Pb, Cd, Cr and As was mainly attributed to electronic information manufacturing activities, while the enrichment of Zn, Cu and Cd was associated with the application of commercial fertilizers and pesticides. The health risk associated with vegetable intake decreased in the order of leafy > fruit > leguminous > root vegetables. Leafy vegetables were identified as the category with the highest risk, with the mean risk value of 1.26. Cd was the major risk element for leafy vegetables. The non-carcinogenic risks estimated for leguminous and root vegetables were under the acceptable level. In conclusion, special attention should be paid to the health risks of toxic metal(loid)s in leafy vegetables in peri-urban areas with intense electronic information manufacturing activities. In order to minimize health risk, it is necessary to identify low-risk crops based on a comprehensive consideration of the metal(loid)s' pollution characteristics, transfer factors and local people's consumption behaviors. Graphical abstract: Image 1 Highlights: Metal(loid)s levels in paired vegetables and soils were observed. Cd and Pb in vegetables and soils were present at relatively high levels. The bioaccumulation ability varied widely among metal(loid)s and vegetable types. Leafy vegetable was identified to be the risk vegetable. The consumption of homegrown vegetables poses health risk to local people.